To a question of menopausal disorders treatment in women of the late reproductive age - Татарчук, Т. Ф; Ефименко, О. А.; Исламова, А. О. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
A study of using the drug Sagenit in women reproductive age with climacteric syndrome was done. We observed 50 patients aged 37–49 years with climacteric disorders mild to moderate severity. Treatment lasts for a one month. Effectiveness of the drug was evaluated at 1 and 3 months after treatment. Sagenit proved highly effective in the treatment of «classical» estrogen deficiency manifestations (sweating and hot flushes), as well as in elimination of neurovegetative and psycho-emotional symptoms. There were not observed side effects and reactions of individual intolerance during monitoring of patients. The obtained results of the study demonstrate the feasibility of using the drug Sagenit in women reproductive age in order to correct menopausal disorders mild to moderate severity.